Study of the Mechanical Properties of Chitosan/Onggok Starch (Arenga Pinnata) Biocomposite Films Reinforced with Cellulose from Rice Straw - Nur Hidayati; Deni Wila Awwalian; Nabilah Miftachul Jannah (Universitas Muhammadiyah Purwokerto, 2024)
Bioplastics are biodegradable polymers derived from biomass sources, and starch is the substrate of choice for bioplastic production because of its ability to decompose into environmentally friendly compounds. Nevertheless, bioplastic films composed solely of starch demonstrate hydrophilic characteristics and are highly vulnerable to water, leading to insufficient durability. In order to enhance the mechanical integrity, this issue is resolved by blending polymers and integrating cellulose into the bioplastic structure. The objective of this study is to investigate the effects of incorporating cellulose at different percentages ranging from 3% to 20% on the mechanical capabilities, water absorption capacity, and biodegradation properties of the onggok chitosan-starch biocomposite. Overall, the addition of cellulose to bio-composite significantly impacts these characteristics.